Analisis Retorika Dakwah Gus Miftah dalam Pengajian pada Channel Youtube @Gus Miftah Official - Sofa Rahmadayani Nasution; Nanang Arianto; Susanti Hasibuan (Kartika: Jurnal Studi Keislaman, 2026)
The development of digital media has transformed the pattern of da’wah communication in society. Da’wah which was previously delivered conventionally, has now expanded through social media platforms such as Youtube. Gus Miftah is one of the contemporary islamic preachers known for his distinctive, humorous, inclusive, and community oriented rhetorical style.This study aims to analyze the da’wah rhetoric of Gus Miftah on the Youtube channel @Gus Miftah Official. This research employs a descriptive qualitative method with a digital ethnography approach and Norman Fairclough’s critical discourse analysis. Aristoteles rhetorical theory consisting of ethos, pathos, and logos is used as the main analytical framework. The research data were obtained from Gus Mifta’s preaching videos uploaded in 2024 on the @Gus Miftah Official Youtube Channel. The findings indicate that Gus Miftah applies effective rhetorical strategies through strong self image building, simple and communicative language, relevant humor, and logical as well as contextual arguments. His rhetorical style successfully creates emotional closeness with audiences and broadens the reach of da’wah in the digital era. Furthermore, the use of Youtube as a medium of da’wah provides wider interaction between preachers and society. This study concludes that Gus Miftah’s da’wah rhetoric represents an adaptive model of digital da’wah that aligns with the development of social media and the needs of modern society